PENGARUH BRAND IMAGE DAN PROMOTION TERHADAP PURCHASE DECISION MEMILIH PRODUK ASURANSI SYARIAH (STUDI PADA PT. ASURANSI JIWA SYARIAH AL-AMIN KANTOR PEMASARAN PADANG) - Benny Aditya Nanda; Septria Susanti (CV. Adiba Aisha Amira, 2025)
This research is motivated by the number of Sharia insurance customers at PT. Al-Amin Padang Sharia Life Insurance depends on the collaborating agencies. The increase and decrease in customers depends on the collaborating agencies. Promotion is also inadequate due to the lack of effective advertising placement which only depends on the agencies collaborating with the company. And there is a research gap compared to before. This research aims to determine the influence of Brand Image and Promotion on Purchase Decisions in choosing Sharia Insurance products at Pt. Al-Amin Padang Sharia Life Insurance. This research uses quantitative research methods. The data source is primary data obtained from observations and distributing questionnaires via Google Form. Data was distributed to 99 Sharia life insurance customers. Based on the results of research at a significance level of 5%, it shows that Brand Image has a significant positive effect on Purchase Decisions. This is proven by the Tcount value being greater than Ttable (18,984 > 1,984). and Promotion has a significant positive effect on Purchase Decisions. This is proven by the Tcount value being greater than Ttable (8,837 > 1,984). This means that the better the promotion is, the more product purchase decisions can be made. Brand Image and Promotion both have a significant positive effect on Purchase Decisions. This is proven by the value of Fcount > Ftable = 195,562 > 3.09. This means that the better the Brand Image and Promotion, the product Purchase Decision can increase. The results of this research can be used by PT. Al-Amin Sharia Life Insurance Padang Marketing Office to formulate marketing strategies that are more targeted, effective and efficient so as to increase the number of customers.